ANALISIS FAKTOR KRITIS YANG MEMPENGARUHI MINAT PENGGUNAAN E-SPT PADA PENGUSAHA MIKRO DI KOTA MADIUN - RIZKA AULIA; EKARISTI SOVI LESTARI; RENALDO RICKO JONATHAN; THERESIA PURBANDARI (Jurnal Keuangan dan Bisnis, 2019)
The purpose of this study is to prove whether ease of use, perceived usefulness, and computer self-efficacy influence the interest in using e-SPT for micro-entrepreneurs in the city of Madiun. The sampling technique used was purposive sampling. To test the hypothesis multiple regression analysis techniques are used. From the results of data processing through SPSS Version 22, namely through the t-test obtained a significant value for ease of use: 0.755, perceptions of use 0.000, and computer self-efficacy 0.038. Based on these results it can be said that the perception variables of use and computer self-efficacy influence the interest in using e-SPT in the City of Madiun, while the ease of use does not affect the interest in using e-SPT in the City of Madiun.